Behind the Scenes of Affiliate Marketing: The Hidden Exploits Behind Commissions - Nugrahanti, Erma Diah Putri; Rahman, Taufiqur (Komunikator, 2026)
Affiliate marketing has rapidly evolved into one of the most prominent digital business models, offering income opportunities through the promotion of products or services on social media platforms. TikTok Shop, as one of the most popular platforms among young creators, has become a dynamic space for these practices to thrive. This study aims to analyze the work dynamics of TikTok Shop affiliates and uncover the practices of digital exploitation within this ecosystem, particularly from the perspective of digital business ethics. Using a virtual ethnography approach, this research involves participatory observation within affiliate communities and digital content analysis, including promotional videos, captions, comments, and discussions taking place on platforms such as Telegram, Facebook, and other digital spaces. The analysis focuses on dominant themes emerging in affiliates’ self-representations, digital labor narratives, adaptation strategies to platform algorithms, and responses to policy changes. The findings reveal that affiliates often face algorithmic pressures, financial uncertainty due to the lack of commission transparency, and limited product choices due to exclusivity systems. The absence of adequate platform support further exacerbates their vulnerability as digital workers. This study highlights that the power imbalance between affiliates and the platform significantly impacts working conditions and affiliate well-being.